2019
DOI: 10.1111/1462-2920.14870
|View full text |Cite
|
Sign up to set email alerts
|

Microbial signatures of protected and impacted Northern Caribbean reefs: changes from Cuba to the Florida Keys

Abstract: There are a few baseline reef-systems available for understanding the microbiology of healthy coral reefs and their surrounding seawater. Here, we examined the seawater microbial ecology of 25 Northern Caribbean reefs varying in human impact and protection in Cuba and the Florida Keys, USA, by measuring nutrient concentrations, microbial abundances, and respiration rates as well as sequencing bacterial and archaeal amplicons and community functional genes. Overall, seawater microbial composition and biogeochem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
31
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(52 citation statements)
references
References 81 publications
4
31
4
Order By: Relevance
“…Thus, the high abundance of dinoflagellates in the waters of a region that has a large tourism industry is of critical concern, not only in relation to SCTLD, but also in relation to other human interests. Our study indicates that dinoflagellate contributed to a larger fraction of the EMC compared to abundances reported by a study that was carried out in the Florida Keys three years earlier [39]. While this difference could just result from variations in seasonal abundances or differences in sampling locations, a regular monitoring program would be appropriate to assess changes in the relative abundances of these organisms in the waters of South Florida.…”
Section: Discussioncontrasting
confidence: 44%
See 2 more Smart Citations
“…Thus, the high abundance of dinoflagellates in the waters of a region that has a large tourism industry is of critical concern, not only in relation to SCTLD, but also in relation to other human interests. Our study indicates that dinoflagellate contributed to a larger fraction of the EMC compared to abundances reported by a study that was carried out in the Florida Keys three years earlier [39]. While this difference could just result from variations in seasonal abundances or differences in sampling locations, a regular monitoring program would be appropriate to assess changes in the relative abundances of these organisms in the waters of South Florida.…”
Section: Discussioncontrasting
confidence: 44%
“…The importance of organic carbon for microbial community structure was also well demonstrated by our data, as TOC concentrations had a significant impact on both prokaryotic and eukaryotic microbial community composition, together with temperature and DO concentrations. Weber et al [39] expected to find significantly higher abundances of heterotrophic bacteria and archaea as a sign of microbialization of reefs in Florida and the Northern Caribbean, which was not the case. Also, the data presented in this study show that the total abundances of unpigmented cells are not necessarily correlated with organic carbon concentrations, and, even though higher abundances of HNA bacteria were more likely to be found in areas with elevated TOC concentrations, this trend was not consistent.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Higher nutrient availability also enriched for nutrient-related microbial metabolic traits such as nitrate and nitrite ammonification 29 . In the Caribbean, microbial signatures were also clearly distinct between protected and offshore Cuban reefs compared to human impacted reefs in the Florida Keys 18 . Similarly, a study across three ocean basins observed that algal-dominated sites were enriched in copiotrophic microbial taxa, including Gammaproteobacterial families such as Enterobacteriaceae, Vibrionaceae, Shewanellaceae and Pasteurellaceae, and Bacteroidetes such as Cytophagaceae and Flavobacteriaceae, whereas coral-dominated reefs were enriched in oligotrophic Alphaproteobacterial families such as Caulobacteriaceae, Sphingomonadaceae, Hyphomonadaceae, Bradyrhizobiaceae, Acetobacteriaceae, Phyllobacteriaceae, Rhodospirillaceae, Pelagibacteraceae, Rhizobiaceae and Rhodobacteriaceae 26 .…”
mentioning
confidence: 97%
“…However, their contribution to the functioning and resilience of reefs is not well understood [12][13][14] . Shifts in the compositional and functional diversity of both coralassociated 15,16 and free-living planktonic 12,17 microbial communities have been linked to varying levels of anthropogenic impact, including changes in seawater nutrient levels 18 . For example, chronic nutrient exposure has been correlated with increased prevalence of coral disease in Caribbean reef systems 19 .…”
mentioning
confidence: 99%